Analisis Rantai Pasok Ternak Sapi Potong di Kecamatan Miomaffo Barat, Kabuapten Timor Tengah Utara, Nusa Tenggara Timur - Tahuk, Paulus Klau; Berek, Dominggus; Sikone, Hilarius Y. (Bantara Journal of Animal Science, 2023)
The purpose of this study was to determine product flow, financial flow, and information flow in the supply chain of beef cattle in West Miomaffo District. This research was conducted in West Miomaffo District in August 2020. This location was determined purposively (intentionally) based on the consideration that West Miomaffo District is one of the 10th (ten) largest beef cattle production centers or 4.04% of the total livestock population beef cattle and has a livestock traffic monitoring post facility with the duties and functions of monitoring the buying and selling activity of cattle crossing land from the TTU area. The type of data that is often used in this research is quantitative data in the form of numerical data, the value of which can change or be varied. In this study the method used was: survey data collection which was carried out by interviewing respondents using a questionnaire so that between researchers and respondents could communicate directly. Data analysis was carried out descriptively which refers to the supply chain of beef cattle. Based on the results of this study it was concluded that there were 40 livestock farmers consisting of 10 collectors, 2 inter-island traders, in West Miomaffo sub-district. The supply chain has a product flow of 2 channel networks, namely: Farmers, breeders, traders, collectors, inter-island traders. Farmers breeders-collectors-traders slaughter livestock. And there are 2 channel networks in the financial flow, namely: Livestock slaughter traders-collecting traders-breeding farmers. Inter-island traders-livestock traders-breeders. As well as the flow of information that moves from two directions from producers to consumers and consumers to producers.